2022
DOI: 10.21079/11681/45484
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of climatic and hydroclimatic resources to support the US Army Corps of Engineers Regulatory Program

Abstract: Short-term climatic and hydrologic interactions, or hydroclimatology, are an important consideration when delineating the geographic extent of aquatic resources and assessing whether an aquatic resource is a jurisdictional water of the United States (WOTUS) and is therefore subject to the Clean Water Act (CWA). The now vacated 2020 Navigable Waters Protection Rule (NWPR) required the evaluation of precipitation and other hydroclimatic conditions to assess the jurisdictional status of an aquatic resource based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Because Sparrow et al. (2022) found no evidence that the APT watershed analysis provides additional skill, when compared to an APT single‐point analysis, the APT watershed analysis was omitted in this study, and instead the study focused on the APT single‐point results.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because Sparrow et al. (2022) found no evidence that the APT watershed analysis provides additional skill, when compared to an APT single‐point analysis, the APT watershed analysis was omitted in this study, and instead the study focused on the APT single‐point results.…”
Section: Methodsmentioning
confidence: 99%
“…However, Sparrow et al. (2022) screened the usefulness of the APT in determining streamflow normalcy and found that the APT's Antecedent Precipitation Score and the queried the National Oceanic and Atmospheric Administration (NOAA) Climate Divisional Database (nClimDiv) Palmer Drought Severity Index (PDSI) (NOAA, 2014) were not strong indicators of daily streamflow percentiles and were typically poor estimators of below normal, normal, and above normal streamflow conditions. Thus, there appears to be a gap in the available data for determining streamflow normalcy in ungaged streams.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The user should consult multiple lines of evidence, in combination with APT, when analyzing the hydroclimatology of their observation point. Additional lines of evidence are cataloged and described by Sparrow et. al (2022).…”
Section: Us Geologicalmentioning
confidence: 99%